ANALISIS HARGA POKOK PRODUKSI, PENDAPATAN DAN BAURAN PEMASARAN AGROINDUSTRI TEMPE DI KELURAHAN YOSODADI, KECAMATAN METRO TIMUR, KOTA METRO - Gita Dhika Citra Putri Andini; Wuryaningsih Dwi Sayekti; Suriaty Situmorang (Lampung University, 2024)
This study aims to analyze the cost of production, income and marketing mix of tempe agroindustry. This study uses the census method for household clusters according to BPS which are classified into 3 levels, namely small, medium and large. Determination of the research location was chosen purposefully. The population in this study were 19 tempe agroindustries. Respondents in this study were the owners of the tempe agroindustry in Yosodadi, East Metro, Metro City. Field data collecting was carried out in August 2019. The data collected in this study were primary and secondary data. The data was analyzed with quantitative and qualitative descriptive methods. The results showed that the cost of production of tempe agroindustry in Yosodadi, East Metro, Metro City in the small cluster was IDR3,399.40/kilogram, while in the medium cluster was IDR3,521.97/kilogram and in the large cluster was IDR3,351.05/kilogram, tempe agroindustry in Yosodadi Village, East Metro, Metro City is a profitable industry and the marketing mix applied by tempe agroindustry in Yosodadi Village, East Metro, Metro City is not using the cluster method because the types and prices of products in all agroindustries are almost the same.Keywords: agroindustry, cost, income, marketing mix, tempe